A performance comparison of euclidean, manhattan and minkowski distances in k-means clustering - Haviluddin Haviluddin; Muhammad Iqbal; Gubtha Mahendra Putra; Novianti Puspitasari; Hario Jati Setyadi; Felix Andika Dwiyanto; Aji Prasetya Wibawa; Rayner Alfred (Institute of Electrical and Electronics Engineers, 2021)
The Indonesian police department has a role in maintaining security and law enforcement under the Republic of Indonesia Law Number 2 of 2002. In this study, data on the crime rate in the Bontang City area has been analyzed. It becomes the basis for the Police in anticipating various crimes. The K-Means algorithm is used for data analysis. Based on the test results, there are three levels of crime: high, medium, and low. According to the analysis, the high crime rate in the Bontang City area is special case theft and vehicle theft. Furthermore, it becomes the police program to maintain personal and vehicle safety.